Phase angle and other vectors of bioelectrical impedance behavior and its relations with metabolism markers of eccentric muscle damage after ischemic preconditioning: Randomized placebo-controlled clinical trial - Vendrame, Julia Waszczuk [UNESP]; Pizzo Junior, Eduardo [UNESP]; Cavina, Allysiê Priscilla de Souza [UNESP]; Teixeira Filho, Carlos Alberto Toledo [UNESP]; Biral, Taíse Mendes [UNESP]; da Silva, Gabriel Martins [UNESP]; Matsumoto, Renan Alves [UNESP]; Brandão, Guilherme Henrique da Silva [UNESP]; Vanderlei, Franciele Marques [UNESP] (Elsevier, 2024)
Background/Objective: Eccentric Exercise (EE) can induce muscle damage, but ischemic preconditioning (IPC) emerge as a valuable approach to hasten the recovery process. Monitoring serum markers of muscle damage and assessing cellular health are essential to evaluate the effectiveness of this approach. Therefore, this study aimed to evaluate the behavior of cellular responses through bioelectrical impedance (BIA) vectors after IPC at different occlusion pressures and correlate them with indirect markers of eccentric muscle damage as creatine kinase (CK) and lactate dehydrogenase (LDH). Methods: Eighty men were divided into four groups: IPC with arterial occlusion pressure (AOP), IPC with 40 % above AOP, placebo, and control. All groups underwent an EE protocol and were evaluated for CK, LDH, and BIA. Repeated measures analysis of variance was used, and correlations were performed using Pearson or Spearman correlation depending on data normality. The significance level was set at p < 0.05. Results: The placebo and control groups showed an increase in CK and LDH levels, along with a decrease in cellular integrity. The IPC-AOP group exhibited an increase in CK and LDH levels, but without negative impact on resistance, integrity, and cellular health. The IPC-40 % group showed an increase in CK, decrease in cellular health, elevation of LDH, and higher tissue electrical resistance. Conclusion: The interventions were not effective in maintaining cellular health in the context of eccentric muscle damage.
Keywords: Blood lactate; Creatine kinase; Electrical bioimpedance; Ischemic preconditioning; Physiological stress; Therapeutic occlusion